Neutrophil and Granulocytic Myeloid-Derived Suppressor Cell-Mediated T Cell Suppression Significantly Contributes to Immune Dysregulation in Common Variable Immunodeficiency Disorders - Vlkova, Marcela; Chovancova, Zita; Nechvatalova, Jana; Connelly, Ashley Nicole; Davis, Marcus Darrell; Slanina, Peter; Travnickova, Lucie; Litzman, Marek; Grymova, Tereza; Soucek, Premysl; Freiberger, Tomas; Litzman, Jiri; et al. (Journal of immunology (Baltimore, Md., 2019)
Common variable immunodeficiency disorders (CVID) represent a group of primary immunodeficiency diseases characterized by hypogammaglobulinemia and impaired specific Ab response, resulting in recurrent infections due to dysfunctional immune response. The specific mechanisms mediating immune deficiency in CVID remain to be determined. Previous studies indicated that immune dysregulation in CVID patients is associated with chronic microbial translocation, systemic immune activation, and altered homeostasis of lymphocytic and myeloid lineages. A detailed phenotypic, functional characterization of plasma markers and immune cell populations was performed in 46 CVID patients and 44 healthy donors. CVID patients displayed significantly elevated plasma levels of a marker of neutrophil activation neutrophil gelatinase-associated lipocalin. Neutrophils from CVID patients exhibited elevated surface levels of CD11b and PD-L1 and decreased levels of CD62L, CD16, and CD80, consistent with a phenotype of activated neutrophils with suppressive properties. Neutrophils from CVID patients actively suppressed T cell activation and release of IFN-γ via the production of reactive oxygen species. Furthermore, CVID was associated with an increased frequency of low-density neutrophils (LDNs)/granulocytic myeloid-derived suppressor cells. LDN/granulocytic myeloid-derived suppressor cell frequency in CVID patients correlated with reduced T cell responsiveness. Exogenous stimulation of whole blood with bacterial LPS emulated some but not all of the phenotypic changes observed on neutrophils from CVID patients and induced neutrophil population with LDN phenotype. The presented data demonstrate that neutrophils in the blood of CVID patients acquire an activated phenotype and exert potent T cell suppressive activity. Specific targeting of myeloid cell-derived suppressor activity represents a novel potential therapeutic strategy for CVID.
Keywords: Young Adult; CD11b Antigen; Male; Immune Tolerance; mladý dospělý; reaktivní formy kyslíku; B7-H1 Antigen; aktivace neutrofilů; granulocyty; Adult; Aged; dospělí; antigeny CD11b; senioři; mužské pohlaví; běžná variabilní imunodeficience; Common Variable Immunodeficiency; T-lymfocyty; neutrofily; Reactive Oxygen Species; myeloidní supresorové buňky; kultivované buňky; Neutrophil Activation; senioři nad 80 let; lidé; ženské pohlaví; Humans; Lipocalin-2; Aged, 80 and over; antigeny CD274; imunologická tolerance; lipokalin-2; Granulocytes; Neutrophils; Cells, Cultured; T-Lymphocytes; Female; lidé středního věku; Middle Aged; Myeloid-Derived Suppressor Cells